2020
DOI: 10.1017/s0954579420001686
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and longitudinal effects of maltreatment on systemic inflammation in young children

Abstract: Exposure to child maltreatment increases the risk for psychiatric and physical diseases. Inflammation has been proposed as a mechanism through which early adverse experiences become biologically embedded. However, most studies providing evidence for the link between early adverse exposures and inflammation have been retrospective or cross-sectional in design, or did not assess inflammation immediately after maltreatment in young children. In the present study we investigated the association between childhood m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…In our study, children were pre-pubertal and, therefore, the main effect of sex cannot be attributed to sex hormones. Of note, we recently observed sex differences in levels of inflammation as a function of maltreatment in our current cohort, as evidenced by elevated levels of C-reactive protein over 24 months among maltreated girls as compared to non-maltreated girls and maltreated and non-maltreated boys ( Entringer et al, 2020 ). Increased inflammatory signaling in girls may contribute to sex differences in epigenetic ageing ( Quach et al, 2017 ); however, we did not see an interaction effect of sex and maltreatment in our study in the prediction of epigenetic ageing.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In our study, children were pre-pubertal and, therefore, the main effect of sex cannot be attributed to sex hormones. Of note, we recently observed sex differences in levels of inflammation as a function of maltreatment in our current cohort, as evidenced by elevated levels of C-reactive protein over 24 months among maltreated girls as compared to non-maltreated girls and maltreated and non-maltreated boys ( Entringer et al, 2020 ). Increased inflammatory signaling in girls may contribute to sex differences in epigenetic ageing ( Quach et al, 2017 ); however, we did not see an interaction effect of sex and maltreatment in our study in the prediction of epigenetic ageing.…”
Section: Discussionmentioning
confidence: 50%
“…Stratified effects as a function of the co-occurrence of major depression and ELS have been observed for glucocorticoid signaling and systemic inflammation in adults ( Heim et al, 2008 ; Danese et al, 2008 ). Systemic inflammation, as evidenced by elevated levels of C-reactive protein, has been reported for children as young as 3–5 years of age as a correlate of maltreatment ( Danese et al, 2011 ; Entringer et al, 2020 ). There is evidence that glucocorticoids and immune mediators are drivers of epigenetic ageing ( Horvath and Raj, 2018 ; Quach et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ehrlich et al (2021) found an association between maltreatment and inflammation in 8-12-year-old girls, but there was no association present in boys. In another study, Entringer et al (2020) reported similar findings; among 3-5-year-olds who were studied prospectively immediately after experiencing maltreatment, they found an association between maltreatment and CRP only in girls but not boys. Most recently, Renna et al (2021) assessed the relationship between childhood abuse and inflammation trajectories over time and found that those who had experienced abuse in childhood exhibited steeper rises in inflammation across time than those who did not experience any type of abuse.…”
Section: Harsh Family Environments and Adverse Childhood Experiencesmentioning
confidence: 54%
“…But how early in life can immune and endocrine system dysregulation be detected and how long does the dysregulation last? Although the longitudinal PNI literature in youth is still limited, initial research has demonstrated that the relationship between childhood chronic stress exposure and immune system dysregulation begins to emerge as early as age 3 ( Entringer et al., 2020 ). When assessed longitudinally between ages 9 to 16, adolescents with more cumulative adversity had greater increases in CRP across this seven-year period ( Copeland et al., 2014 ).…”
Section: Pni Models In Childrenmentioning
confidence: 99%
“…Measures with low administrator burden that are language independent to reduce cultural biases are preferred, such as the International Guide for Monitoring Child Development and Cambridge Automated Neuropsychological Test and Battery ( Ozturk Ertem et al., 2019 ; Syvaoja et al., 2015 ). Peripheral levels of CRP and cortisol also are recommended additional screening measures of immune and HPA axis functioning, as they have been identified as persistent markers of stress in early childhood ( Entringer et al., 2020 ; Hunter et al., 2011 ; Slopen et al., 2013 ). They are commonly assessed on standard blood and salivary panels, which decreases the barriers of adding them to regularly performed screenings.…”
Section: Screening For Pni Markers Of Riskmentioning
confidence: 99%